Transmedia storytelling as an empowerment and social change tool in Colombia: BioCuenca alliance case [La narrativa transmedia como herramienta de empoderamiento y cambio social en Colombia: Caso Alianza BioCuenca] (2018)
This study examines if there was a significant statistical relation between people's knowledge of the importance of protecting water basins and their participation in educational campaigns to promote social change focused on preserving the environment and protecting its natural resources. In addition, this study analyzes whether there is a significant statistical relation between people's knowledge regarding modern Information and Communication Technologies (ICT) and their participation in fundraising campaigns that promote environmental protection and that include transmedia storytelling among their strategies. Finally, it is analyzed if people's knowledge regarding the importance of protecting water basins and the information and communication technologies together predict the degree of participation of the population in fundraising campaigns. In short, it was found that there is an association between the knowledge of watershed protection and the participation in educational campaigns that promote protecting the environment and its natural resources. It was observed that there is an association between the knowledge of de population about ICTs and their participation in fundraising campaigns that include transmedia storytelling among their strategies. Finally, the regression analysis demonstrated that knowledge of ICTs predicts the degree of participation of the population in fundraising campaigns. © 2018 Universidad de Caldas. All rights reserved.